Effects of a multi-component nutritional telemonitoring intervention on nutritional status, diet quality, physical functioning and quality of life of community-dwelling older adults. Issue 10 (15th May 2018) - van Doorn-van Atten, Marije N.; Haveman-Nies, Annemien; van Bakel, Marit M.; Ferry, Monique; Franco, Maite; de Groot, Lisette C. P. G. M.; de Vries, Jeanne H. M.
Abstract: This study aimed to evaluate the effects of an intervention including nutritional telemonitoring, nutrition education, and follow-up by a nurse on nutritional status, diet quality, appetite, physical functioning and quality of life of Dutch community-dwelling elderly. We used a parallel arm pre-test post-test design with 214 older adults (average age 80 years) who were allocated to the intervention group ( n 97) or control group ( n 107), based on the municipality. The intervention group received a 6-month intervention including telemonitoring measurements, nutrition education and follow-up by a nurse. Effect measurements took place at baseline, after 4·5 months, and at the end of the study. The intervention improved nutritional status of participants at risk of undernutrition ( β (T1)=2·55; 95 % CI 1·41, 3·68; β (T2)=1·77; 95 % CI 0·60, 2·94) and scores for compliance with Dutch guidelines for the intake of vegetables ( β =1·27; 95 % CI 0·49, 2·05), fruit ( β =1·24; 95 % CI 0·60, 1·88), dietary fibre ( β =1·13; 95 % CI 0·70, 1·57), protein ( β =1·20; 95 % CI 0·15, 2·24) and physical activity ( β =2·13; 95 % CI 0·98, 3·29). The intervention did not have an effect on body weight, appetite, physical functioning and quality of life. In conclusion, this intervention leads to improved nutritional status in older adults at risk of undernutrition, and to improved diet quality and physical activity levels of community-dwelling elderly. Future studies with a longer duration should focus on older adults at higher risk of undernutrition than this study population to investigate whether the impact of the intervention on nutritional and functional outcomes can be improved.